2017
DOI: 10.1167/iovs.16-21230
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacodynamic Analysis of Choroidal Neovascularization in a Porcine Model Using Three Targeted Drugs

Abstract: PurposeTo compare the efficacy of microneedle-delivered suprachoroidal (SC) pazopanib to intravitreal (Ivit) delivery of pazopanib, bevacizumab, or a fusion protein hI-con1 versus vehicle controls on choroidal neovascularization (CNV) growth in a pig model.MethodsForty-one pigs were injected on the day of CNV induction (hI-con1 on postinduction day 14) with either 2.5 mg Ivit bevacizumab (n = 9), 1 mg Ivit pazopanib (n = 9), 300 Ivit μg hI-con1 (n = 4), or 1 mg SC pazopanib (n = 9), vs. 10 vehicle controls (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The rapid development of OCT technology since its inception in 1991 has provided exquisite methods to identify and evaluate multiple layers of the eye wall and eye tissue, including the vitreoretinal interface, retina, RPE, Bruch membrane, and choroid (Huang et al, 1991). The pig is being employed increasingly as a large animal model for experimental and preclinical studies for human diseases, including retinal vascular (Hein et al, 2012; Hein et al, 2010; Hein et al, 2016) and degenerative diseases (Mones et al, 2016; Scott et al, 2014), and choroidal neovascularization (Tran et al, 2017). Despite the widespread adoption of SD-OCT instrumentation in research laboratories, histologic correlation of the porcine retina with SD-OCT data remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of OCT technology since its inception in 1991 has provided exquisite methods to identify and evaluate multiple layers of the eye wall and eye tissue, including the vitreoretinal interface, retina, RPE, Bruch membrane, and choroid (Huang et al, 1991). The pig is being employed increasingly as a large animal model for experimental and preclinical studies for human diseases, including retinal vascular (Hein et al, 2012; Hein et al, 2010; Hein et al, 2016) and degenerative diseases (Mones et al, 2016; Scott et al, 2014), and choroidal neovascularization (Tran et al, 2017). Despite the widespread adoption of SD-OCT instrumentation in research laboratories, histologic correlation of the porcine retina with SD-OCT data remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the antibodies described herein could also be prioritized for the treatment of other diseases associated with upregulation of membranous TF expression, such as macular degeneration (49). A FVII-Fc fusion protein that binds TF reduces the size of choroid neovascular (CNV) lesions in various animal models (50,51). With the binding affinities of a subset of the anti-TF antibodies below the affinity of FVII for TF (52), some of the antibodies could be more efficacious than the FVII-Fc fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…SCS delivery can result in high bioavailability in the sclera, choroid, and RPE[28, 32, 36, 59, 61, 66, 6870, 88, 89]. For example, a small molecule HIF-1 inhibitor injected into the SCS of rats distributed throughout the choroid and retina, and prevented choroidal neovascularization in an animal model with selective destruction of Bruch’s membrane[69].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…No studies have yet used SCS delivery for therapeutic effect on the RPE. Studies have shown that choroidal neovascularization is more effectively treated with intravitreal injections of a receptor tyrosine kinase inhibitor than SCS injections, although the authors noted incomplete delivery with the SCS injection[89]. …”
Section: Pharmacodynamicsmentioning
confidence: 99%